Cymbidium jiangchengense (Orchidaceae; Epidendroideae; Cymbidiinae), a new species from China: evidence from morphology and DNA sequences - Peng, Ying-Li; Zhou, Zhuang; Lan, Si-Ren; Liu, Zhong-Jian (Phytotaxa, 2019)
A new orchid species, Cymbidium jiangchengense, from Yunnan Province, China, is described and illustrated. Its distinctiveness is evaluated with morphology and molecular analyses. A detailed comparison between the newly discovered orchid and other members of Cymbidium was performed. The new plant was characterized by stem-like pseudobulbs, narrowly oblong leaves, coriaceous leaves with an acute apex, a 2-flowered inflorescence, a purplish pink flower, narrowly elliptic sepals, petals, a obovate-lanceolate lip with a cordate midlobe, a yellow central callus, and a disc with a trough shape longitudinal lamella from the base extending to the base of the midlobe and a lamellae apex inflated to form two calluses that are not confluent apically. These features distinguish this new orchid from all other known species of Cymbidium. A molecular study based on nuclear ribosomal ITS and plastid matK and rbcL DNA sequence data indicates that C. jiangchengense is a distinct species that sister to C. wadae and a member of section Eburnea, subgenus Cyperorchis.